1986
DOI: 10.1007/bf01001779
|View full text |Cite
|
Sign up to set email alerts
|

Peroxidative aggregation of myelin membrane proteins

Abstract: The exposure of CNS myelin to reactive oxygen species (ROS) generated by a Cu2+-H2O2 system results in the aggregation of membrane proteins. Integral and peripheral membrane proteins are equally vulnerable and the denaturation is not mediated by the SH groups. The aggregated proteins retain their original antigenicity as determined by immunoblot technique. The aggregation of proteins is not limited to myelin and can be elicited in the preparation of other cerebral membranes. The effect of ROS on membrane prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1987
1987
2002
2002

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…It has also been shown that the changes observed in myelin during aging can be reproduced in in vitro oxidation experiments [68]. In vitro oxidation of isolated myelin by free radicals pro duces a decrease in the major myelin proteins [69], lead ing to the formation of molecular aggregates of these proteins. These investigators proposed that the oxidative damage could produce aggregation of PLP.…”
Section: Astrocytes and Neuronesmentioning
confidence: 90%
“…It has also been shown that the changes observed in myelin during aging can be reproduced in in vitro oxidation experiments [68]. In vitro oxidation of isolated myelin by free radicals pro duces a decrease in the major myelin proteins [69], lead ing to the formation of molecular aggregates of these proteins. These investigators proposed that the oxidative damage could produce aggregation of PLP.…”
Section: Astrocytes and Neuronesmentioning
confidence: 90%
“…Furthermore, antioxidants are low in nerve, and depleted by ROS, leaving the nerves at risk for ROS damage ( Muijsers et al, 1997 ; Romero, 1996 ) . ROS target ion channels, transporters and enzymes ( Konat et al, 1986 ; Kourie, 1998 ; Mattson, 1998 ) , and subtoxic levels facilitate nerve excitability ( Stahl et al, 1993 ) . Increases in ROS have also been implicated in exaggerated pain induced by peripheral nerve injuries ( Khalil et al, 1999 ; Levy et al, 1999 ; Tal, 1996 ; Thomas et al, 1996 ; Wagner et al, 1998 ) (Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…This renders the myelin susceptible to degradation by extracellular proteases liberated by macrophages. Lipid peroxidation and protein nitration are the most destructive result of ROS and NO, as these damage a variety of peripheral nerve structures, including ion channels, ATPases, ion transporters, ion exchangers, glucose transporters, membrane-bound enzymes, and mitochondria (149,154,184). Damaged ion channels and transport systems increase neuronal excitability (154,184,283) and alter a variety of second messenger systems via increases in intracellular calcium (154).…”
Section: Antibody-mediated Nerve Damagementioning
confidence: 99%